γ-Glutamyl transpeptidase-activable nanoprobe crosses the blood-brain barrier for immuno-sonodynamic therapy of glioma - Bo Li; Gengjia Chen; Huihai Zhong; Tan Li; Minzhao Lin; Huiye Wei; Qiaoyun Zhang; Qi Chen; Jinsheng Huang; Xintao Shuai (Nature Communications)
Abstract Effective treatment against glioma remains challenging nowadays because the protective blood-brain barrier (BBB) impedes drug penetration into brain and the limited efficacy of conventional chemotherapy. While strong positively charged nanoparticles have good permeability through the BBB, they often come with the caveat of cationic toxicity to healthy tissues and organs during blood circulation. Here we show a neutrally charged nanoprobe with a surface decorated with γ-glutamyl moieties that can be cleaved by γ-glutamyl transpeptidase, an enzyme overexpressed on brain capillaries. Upon the cleavage, positively charged primary amines are generated, facilitating the effective crossing of the nanoprobe through BBB via the adsorption-mediated transcytosis pathway, while avoiding the caveat of cationic toxicity. In addition, when reaching the acidic tumor microenvironment, the nanoprobe co-encapsulating sonosensitizer and immune agonist swells, which results in an accelerated drug release under ultrasound irradiation to induce a combined immune response, ultimately leading to a robust anticancer effect. Overall, we report an effective drug delivery nanoplatform across the BBB for an enhanced therapy of glioma.